The Effect of Soaking Time of Liquid Smoke on the Quality and Storability of Cow Meat - U Purba; I Sembiring; E Mirwandhono; N Ginting (Talenta Publisher, 2018)
Post harvest quality of cow meat and in storage may changes as consequence of biochemistry and microbiology process. This changes make meat durability and processed products will be limited. So that necessary processing to improve meat durability is needed. This study aimed to test the effect of soaking time of liquid smoke against meat durability meet by tenderness and organoleptic test(texture, aroma, flavor and tenderness). This research was conducted at Laboratory of Food Technology Faculty of Agriculture, University of North Sumatra from Mei to June 2016.The design used in this study was completely randomized factorial design (factorial CRD) using two factors:the soaking time of liquid smoke(A): (5 minutes, 10 minutes and15minutes) and storability(P): (1 week, 2weeks, 3 weeks and4 weeks). The parameters analyzed were cooking shrinkage, tenderness and organoleptic test(texture, aroma, and flavor). The results showed that soaking time of liquid smoke gave highly significant effect (P<0,01) to the organoleptic test (aroma), while storability give highly significant effect (P<0,01) to the cooking shrinkage(%), tenderness, andorganoleptic test(texture, aroma, and flavor).The best results were obtained ats oaking time of liquid smoke 15 minutes.